Ghrelin activates hypophysiotropic corticotropin-releasing factor neurons independently of the arcuate nucleus. (May 2016) - Cabral, Agustina; Portiansky, Enrique; Sánchez-Jaramillo, Edith; Zigman, Jeffrey M.; Perello, Mario
Highlights: Ghrelin-induced activation of PVN CRF neurons does not require NPY signaling and depends on GABA signaling. Ghrelin receptor is located in GABAergic terminals of the PVN, where ghrelin inhibits GABA release. Ghrelin activates PVN CRF neurons but does not increase food intake in ARC-ablated mice. Ghrelin increases food intake but does not activate PVN CRF neurons in mice with GHSR expression in ARC AgRP neurons only. Thus, the neuronal circuits mediating ghrelin's role as an orexigenic vs. a stress signal can be anatomically dissociated. Abstract: Previous work has established that the hormone ghrelin engages the hypothalamic–pituitary–adrenal neuroendocrine axis via activation of corticotropin-releasing factor (CRF) neurons of the hypothalamic paraventricular nucleus (PVN). The neuronal circuitry that mediates this effect of ghrelin is currently unknown. Here, we show that ghrelin-induced activation of PVN CRF neurons involved inhibition of γ-aminobutyric acid (GABA) inputs, likely via ghrelin binding sites that were localized at GABAergic terminals within the PVN. While ghrelin activated PVN CRF neurons in the presence of neuropeptide Y (NPY) receptor antagonists or in arcuate nucleus (ARC)-ablated mice, it failed to do it so in mice with ghrelin receptor expression limited to ARC agouti gene related protein (AgRP)/NPY neurons. These data support the notion that ghrelin activates PVN CRF neurons via inhibition of local GABAergic tone, in an ARC-independent manner. Furthermore, these data suggest that the neuronal circuits mediating ghrelin's orexigenic action vs. its role as a stress signal are anatomically dissociated.